PERSEPSI DAN EKSPEKTASI WISATAWAN MANCANEGARA TERHADAP INDUSTRI RESTORAN DI KABUPATEN BADUNG - I Nyoman Arcana, SE., M.Par (Institut Pariwisata dan Bisnis Internasional, 2014)
This study aims to explore foreign touristâ€™s satisfaction performance, variables determine satisfaction performance, perceptions and expectations towards restaurant industry at Badung Regency, especially at Tanjung Benoa, Nusa Dua, Jimbaran, Kuta, and Seminyak area.Based on previous studies conducted by Dogdubay and Avcikurt (2008), Andaleeb and Conway (2006), Pun and Ho (2001), Kivela, et all (2000), and Cousins (2002), there were 36 performanceâ€™s variables and 4 satisfactionâ€™s variable used in this study which is consist of 7 variables on food quality (reliability), 6 variables on service quality (responsiveness), 3 variables on brands/popularity, 5 variables on convenience, 11 variables on ambiance, and 4 variables onÂ price. Total respondent on this research were 156. The methodology or approach used in this study were â€œmeanâ€ andÂ Important-Performance Analysis.Â This study shows that 3 attributes of satisfactionâ€™s performance located at Quadran A, 17 attributes at Quadran B, 13 attributes pada Kuadran C, and 3 attributes at Quadran D. The result findings in this study indicatesÂ there were 29 attributes with good performance, and 7 attributes with very good performance., and there were 13 attibutes met or over expected, and 23 attributes under expected. Practical implications of this study was that restaurant managers supposedÂ to improve performances on attributes such as: tasty food, friendly/polite/helpful staff, overall cleanliness, toilet, fresh food, consistent standard of food quality, food presentation & garnished, healthy food, speed of service, consistent standard of service quality, location, and view from restaurant.Â